2005
DOI: 10.1002/jbt.20051
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate‐induced developmental toxicity and production of reactive oxygen species in zebrafish embryos

Abstract: Dichloroacetate (DCA) is one of the toxic by products that are formed during the chlorine disinfection process of drinking water. In this study, the developmental toxicity of DCA has been determined in zebrafish (Danio rerio) embryos. Embryos were exposed to different concentrations (4, 8, 16, and 32 mM) of the compound at the 4 h postfertilization (hpf) stage of development, and were observed for different developmental toxic effects at 8, 24, 32, 55, 80, and 144 hpf. Exposure of embryos to 8-32 mM of DCA res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…Earlier reports have shown that DCA causes developmental and reproductive adversities in exposed organisms (rat and zebrafish) wherein very high concentrations of DCA (~400-4,000 mg/kg) were used (Hassoun et al 2005;Linder et al 1997;Smith et al 1992). However, none of the tested DCA concentrations were found to induce developmental and reproductive adversities in exposed Drosophila as evidenced by nonapparent change in the emergence pattern and reproductive performance of exposed flies.…”
Section: Discussionmentioning
confidence: 90%
“…Earlier reports have shown that DCA causes developmental and reproductive adversities in exposed organisms (rat and zebrafish) wherein very high concentrations of DCA (~400-4,000 mg/kg) were used (Hassoun et al 2005;Linder et al 1997;Smith et al 1992). However, none of the tested DCA concentrations were found to induce developmental and reproductive adversities in exposed Drosophila as evidenced by nonapparent change in the emergence pattern and reproductive performance of exposed flies.…”
Section: Discussionmentioning
confidence: 90%
“…These included TCDD (Henry et al, 1997;Belair et al, 2001;Dong et al, 2002Dong et al, , 2004Teraoka et al, 2002Teraoka et al, , 2003Prasch et al, 2003;Antkiewicz et al, 2005;Carney et al, 2006;Ton et al, 2006), benzene and toluene (Mizell et al, 1996;Mizell and Romig, 1997), dichlorvos (Sisman, 2010), and BPA (Duan et al, 2008). Interestingly, PFOS and dichloroacetate exposures at earlier time points (in embryos \ 80 hpf) caused pericardial edema and brachycardia, but resulted in the opposite effect of tachychardia (increased heart rate) if exposures began after 80 hpf (Hassoun et al, 2005;Shi et al, 2008;Huang et al, 2010). Other heart malformations and decreased heart size have been reported to be caused by TCDD (Mizell and Romig, 1997;Antkiewicz et al, 2005;Carney et al, 2006;Mehta et al, 2008), 3,3 0 ,4,4 0 ,5-pentachlorobiphenyl (PCB126) (Grimes et al, 2008), benzene and toluene (Mizell et al, 1996;Mizell and Romig, 1997), and aristolochic acid (Huang et al, 2007) (Table 5).…”
Section: Cardiovascular Developmental Toxicitymentioning
confidence: 95%
“…DCA administration to rats resulted in significant production of lipid peroxidation and DNA damage in hepatic tissues, and those effects were considered to play a possible role in the compound's hepatotoxic and hepatocarcinogenic effects [17,18]. The developmental toxic effects of DCA have been recently described in zebrafish embryos [19]. Those studies have also demonstrated an association between the developmental toxic effects in the DCA-exposed embryos and the overproduction of ROS in the same embryos [19].…”
Section: Introductionmentioning
confidence: 94%
“…The developmental toxic effects of DCA have been recently described in zebrafish embryos [19]. Those studies have also demonstrated an association between the developmental toxic effects in the DCA-exposed embryos and the overproduction of ROS in the same embryos [19].…”
Section: Introductionmentioning
confidence: 96%